Analysis of Hydrogen Production from Glycerol Gasification Using Supercritical and Subcritical Water. - Jan Galvao Gomes; Julles Mitoura dos Santos Junior; Annamaria Doria Souza Vidotti; Antonio Carlos Daltro de Freitas; Reginaldo Guirardello (Chemical Engineering Transactions, 2022)
With the increasing consumption of fossil fuels, two major problems have been worrying the world: energy security and pollution caused by non-renewable fuels. When considering alternative sources of renewable energy, the potential of several biomasses is verified, which have been used in the production of biofuels such as hydrogen (H2). This work will present an analysis on the conversion of glycerol into H2 with gasification in supercritical (SCWG) and subcritical (SbCWG) water using the Gibbs energy minimization (MinG) and entropy maximization (MaxS) methods. These methodologies will be implemented in the Gams software and solved using the CONOPT 4 solver. The cubic Peng Robinson (PR) equation of state was used to evaluate the non-idealities of the phases. The SCWG results showed the most suitable regions to operate in adiabatic (below 900 K) or isothermal (above 900 K) conditions according to the endothermic character of the system. The increase in temperature favors the production of hydrogen while the increase in the initial composition of biomass is unfavorable. Pressure has no major influence on the system. The SbCWG did not show significant production of H2. However, when secondary reactions are inhibited, we observed relevant productions of H2. This highlights the need to use specific catalysts to favor the hydrogen reaction. With this work, we seek to contribute to a better thermodynamic understanding of the relevant effects by reactional pathways of biomass decomposition and sustainable production of H2.